Diagnosis of Biliary Atresia Can Not Be Excluded by Declining Trend of Serum Direct Bilirubin - Terui, Keita; Higashimoto, Yasuyuki; Saito, Eriko; Saito, Takeshi; Mitsuanga, Tetsuya; Nakata, Mitsuyuki; Iwai, Jun; Yoshida, Hideo (Pediatric reports, 2013)
The aim of this paper is to investigate the clinical courses of patients with biliary atresia (BA) during neonatal period. We examined 19 patients with BA, who underwent blood tests including direct bilirubin (D-Bil) within 20 days of age, in 3 tertiary hospitals in Japan. The first blood sample was collected at 8.4±6.5 days of age. The acholic stool was observed within 2 weeks of age in 16 cases (84.2%). Decrease of T-Bil was observed in all the subjects, with a range of reduction of 6.5±3.3 mg/dL, from 10.4±7.5 to 29.8±9.1 days of age. Decrease of D-Bil was also observed in 17 out of 19 cases (89%), with a range of reduction of 1.1±1.0 mg/dL, from 15.5±8.0 to 24.9±9.6 days of age. A significant decrease of D-Bil was observed in 2 cases of biliary atresia splenic malformation syndrome. We therefore conclude that clinicians treating icteric infants should not exclude a diagnosis of BA even if the level of D-Bil has a declining tendency.